Liberdade e individualidade: diálogos contemporâneos com (e a partir de) Max Stirner - Alves, Munis Pedro (2015)
This study is meant to examine, understand and reflect on the philosophical concepts of freedom and individuality in Max Stirner‟s studies. Starting from contemporary issues the study aims to build reflections and dialogues with (and on) Stirner to understand the exercises and constitutions to freedom of individuals and also to point differences between him philosophy and our time , enabling libertarian practices. I intent to investigate modernity issues, updating the reading and reconnecting this literature to the present time, based on the assumption that those aspects relate with current sensibilities via an interaction of temporalities.